Characteristics of beta parapapillary atrophy in primary angle-closure suspect - Qing Zhang; Ye Zhang; Xiaohua Pan; Hui Feng; Shuning Li; Zhi Li; Meijuan Zhang; Caixia Li; Fei Xiang; Qianqian Ji (BMJ Open Ophthalmology)
Objective To investigate the characteristics of beta parapapillary atrophy (β-PPA) in patients with primary angle-closure suspect (PACS).Methods and analysis In total, 215 and 259 eyes with PACS and non-PACS (NPACS), respectively, were enrolled in this observational, cross-sectional study. Stereoscopic fundus and optical coherence tomography images were used to characterise β-PPA; the former was also used to measure the major β-PPA parameters. Univariate and multiple logistic regression analyses were used to identify the factors correlated with the presence of β-PPA and with β-PPA parameters.Results The β-PPA occurrence rates were 48.80% and 44.40% in the PACS and NPACS groups, respectively, with no significant difference between groups. Compared with that in the NPACS group, the β-PPA area was significantly larger (p=0.005) in the PACS group, but the angular extent and maximum radial length did not differ between groups (p=0.110 and 0.657, respectively) after adjusting for age and axial length. The presence of β-PPA was associated with older age (OR 1.057, 95% CI 1.028 to 1.088, p<0.001) and larger disc area (OR 1.716, 95% CI 1.170 to 2.517, p=0.006). A larger β-PPA area was associated with older age (p=0.014), greater vertical cup-to-disc ratio (p=0.028), larger disc area (p<0.001) and PACS diagnosis (p=0.035).Conclusion 48.80% of participants with PACS had β-PPA, which is slightly larger than NPACS. The area of β-PPA was larger in PACS, while the angular extent and maximum radial length did not differ between groups.